Genetic Analysis of the Characters of Intraspecific Similarity - Chadov , B. F.; Fedorova, N. B. (New Advances in Medicine and Medical Science Vol. 8, 2023)
The experiments by Gregor Mendel, which formed the background for genetics, were performed with the characters of intraspecific difference (alternative characters). Mendelian protein-coding genes are responsible for these characters. Until recently, these genes were regarded as the only and main hereditary factors responsible for ontogenesis and phylogenesis. The review outlines the information about another category of biological characters (the characters of intraspecific similarity) and, correspondingly, of a special category of genes responsible for these characters (ontogenes). The human biological sciences are in essence the descriptions of the characters of intraspecific similarity, therefore, ontogenes is of great interest for medicine. The study into mutations of ontogenes in drosophila experiments suggests that (1) ontogenes control the construction of cell ensembles and trigger protein-coding genes in cells; (2) the program of individual development is encoded in ontogenes and “edited” in germline cells; (3) ontogenes fulfill a regulatory function without any contacts and chemical intermediaries, which suggests a kind of biophysical activity; and (4) two categories of cells—stem cells and terminally differentiated cells—correspond to these two categories of genes. Ontogenes are active in stem cells and protein-coding genes, in terminally differentiated cells.